GROWTH AND YIELD RESPONSE OF POTATO (SOLANUM TUBEROSUM L) TO ORGANIC AND BLENDED FERTILIZERS - Muhie, Seid Hussen (Potato Journal, 2023)
ABSTRACT: Appropriate nutrition management of the potato crop is crucial during the entire growth period as part ofa successful agronomic strategy. In places of mid and high altitude where present yields of potato (Solanum tuberosumL.) are less than 10 t ha-1, where production is severely hampered by inadequate soil fertility, Ethiopia has a significantpotential to boost potato production and productivity. A field experiment was conducted to determine the effects ofintegrated application of blended NPS fertilizer and compost on growth, yield parameters and yield of potato (Solanumtuberosum L.), variety ‘Belete’ under irrigation at Efrata Gidim District, North Showa, Ethiopia in 2022 cropping season.The treatments consisted of four Nitrogen-Phosphorus-Sulfur (NPS) blended fertilizer levels (0, 50,100 and 150 kg ha-1) andthree compost levels (0, 10 and 20 t ha-1). The experiment was laid out as a Randomized Complete Block Design (RCBD)in a factorial arrangement and replicated three times. Data were collected and statistically analyzed using SAS version 9.2software. The findings revealed that the highest marketable tuber number per plant (14.1), total tuber number per plant(17.6), marketable tuber yield (13.0 t ha-1) and total tuber yield (15.48 t ha-1) were obtained from combined application of150 kg ha-1 NPS blended fertilizer and 20 t ha-1 compost. The integrated application of nutrients might have benefited thecrop to access the essential elements for growth and development. The result can be temporarily recommended for potatoproducers around the study areas and similar agroecologies.